THE UTILIZATION OF MCH BOOKS BY FAMILIES IN MONITORING THE NUTRITIONAL STATUS OF TODDLERS - Lestari, Sri; Yusita, Intan; Mulyati, Iceu; Oktafiani, Hani; Sugiharti, Ina; Hayati, Ning; Sarbini, Amida (Operations Research: International Conference Series, 2023)
The low nutritional status of toddlers indicates a non-optimal level of health. Family empowerment is the key to toddler care to improve nutritional status. Kia books are an excellent medium for monitoring nutritional status (Susilo et al., 2021). Cibeet Village is the village with the highest cases of malnutrition in the Ibun health center area of Bandung regency with toddler visits to posyandu only 50%. MCH books were used in this study to monitor the nutritional status of toddlers. The study was designed using an analytical crossectional study, with a sample of 57 mothers under five and family. Samples from each of these villages were randomly selected and re-selected from each posyandu. Data related to the use of Kia books by families are carried out through observation of family members and direct measurement of nutritional status. The results showed that mothers of toddlers who used MCH books periodically were 42.1%, mothers were family members who used MCH books 89.5%, nutritional status of toddlers 84.2% were bai k nutrition. Based on the analysis of the relationship between the use of MCH books and the nutritional status of toddlers, a p-value (0.00 0) was obtained, < with an alpha value (0.05). Thus there is a relationship between the use of MCH books and the nutritional status of toddlers. There is a relationship between the use of kia books and toddler caregivers obtained p-value (0.00 4) < alpha value (0.05). Kurang from half of the families of toddlers have not used the MCH book as a medium for determining the nutritional status of toddlers and there are still toddlers with malnutrition, in Cibeet village, the working area of the Ibun Health Center. Efforts are needed to empower families in utilizing Kia books so that family participation increases in maintaining family health.